Decision-making and cash spending patterns of adolescent girls and young women participating in a cash-transfer intervention in Tanzania: Implications for sexual health. Issue 4 (2nd April 2020) - Wamoyi, Joyce; Balvanz, Peter; Gichane, Margaret W.; Maman, Suzanne; Mugunga, Samuel; Majani, Esther; Pettifor, Audrey
ABSTRACT: Although cash transfers (CT) have been recommended as a strategy to address structural drivers of HIV, the evidence of the effects of CT on sexual risk and HIV outcomes is mixed. This could partly be due to CT implementation dynamics and beneficiary interpersonal factors. We conducted an assessment of CT component of the DREAMS programme in Tanzania. We explored how AGYW spent their CT over time, to whom they disclosed cash receipt, and where they sought advice on CT use. The study employed qualitative research methods including: 20 longitudinal in-depth interviews (IDIs) and 60 cross-sectional IDIs with AGYW in the CT programme. Data were analysed thematically. AGYW use of CT fell into five categories: business development, survival, self-care, helping family, and savings. The primary uses of CT funds were investment in businesses and livestock for savings. AGYW use of cash changed over instalments. AGYW consulted a variety of sources when deciding on how to use the cash, primarily mothers, programme personnel, and long-term partners/husbands. CT programmes that give cash directly to AGYW and have a strong entrepreneurial mentorship component could have implications for HIV prevention, SRH, and overall social and economic development.